The image of Thought. The aura of the figure between philosophy and anthropology (Nóema, 2012)
The present essay is an investigation about the rise of the earliest forms of figuration and the relationship they have with the birth of human conceptuality. Through the history of the figure it appears a large fork in history of civilization, the essential bifurcation caused by the two great ways to put the figure at work: on the one hand the operation of the Western sense, enucleated by the analysis of Carlo Sini, on the other the figurative expression of natural changes, caught by Eastern ideogram, which produces an alternative way of meaning, illustrated by Fenollosa and Jullien. By evoking the aura of the two different figurative ways, it tries to draw a genealogy that builds a single image of Thought.
Keywords: filosofia teoretica; archeologia; antropologia; Emmanuel Anati; Marija Gimbutas; scrittura; palaeolithic pictures; prospettiva; Carlo Sini; Gilles Deleuze; ideogramma; Fenollosa; yin; yang; I Ching; Shitao